El estrés laboral y su incidencia en la estabilidad emocional de los docentes de la Unidad Educativa Monseñor Santiago Fernández García, de la ciudad de Cariamanga. Periodo enero-julio 2015 - Torres Rosales, Vanessa Nathalia (2015)
This research presents as objectives: to identify the presence of occupational stress in teachers; assessing emotional stability in them; and designing an intervention plan to deal with work stress among teachers of the Education Unit Monsignor Santiago Fernandez Garcia from Cariamanga city. For this, we use no experimental methodology, cross study with a qualitative-quantitative method approach is required, in addition, two psychological reagents were applied and that contributed to detect and assess the presence of Job Stress and Emotional Stability in a sample of 42 teachers who teach in various areas of education and who belong to a total population of 150 teachers. After applying the reagent we observed that 55% of the sample presents work stress, while 45% don’t have it. As emotional stability, the application of Eysenck test showed that 60% of the sample suffering from emotional instability. Emotional Instability was mainly reflected in factors such as anxiety, obsessiveness, and hypochondriasis. Keywords: Job Stress, Emotional State, emotional instability